Knowledge and Attitude of Parents towards COVID-19 Vaccination Program for Children and Adolescents in Ipoh - Kyaw Ko Latt; Nur Nisha Nadhira Binti Junaidi; Amni Amirah Binti Azlan; Nurul Ezzah Binti Arba’ae; Nurul Insyirah Binti Mohamed Hatta; Nur Izzati Atiqah Binti Abd Samat; Nurul Ain Binti Mohd Rosli; Hussain R.A Saadi; Myo Oo (Asian Journal of Medicine & Health Sciences, 2023)
COVID-19 pandemic caused many deaths due to its high infectivity rate of transmission worldwide. Hence, COVID-19 vaccination program has been implemented which urges children aged above 5 years old to be vaccinated in order to curb the spread of disease and reach herd immunity. However, vaccine refusal or hesitancy among parents for their children pose huge challenges in achieving herd immunity and has put the unvaccinated children on edge which can be seen among Malaysian parents concerning over COVID19 vaccine safety and efficacy for their children. The study was conducted to assess the knowledge and attitude of parents towards COVID-19 vaccination program for children and adolescents in Ipoh. A crosssectional study was conducted involving 244 respondents (parents) in Ipoh through convenience sampling method. The data was collected through an online survey and in hard copy. The questionnaire consisted of three components. They were sociodemographic of respondents, knowledge, and attitude towards COVID19 vaccination for children and adolescents. More than half of the respondents in this study were female (53.7%), with a mean age of 38.7± 6.8 years. Majority were diploma or certificate holders (39.8%), and their main occupations were not health-related (91.8%) with a monthly household income ranging from RM4850 – RM10959 (56.6%). The study showed that more than two-thirds of the respondents (70.1%, n = 171) have good levels of knowledge, while the rest of them (29.9%, n=73) have poor levels of knowledge towards children and adolescents COVID-19 vaccination. Majority of them (86.1%, n=210) showed that they had a good attitude level. The study depicted that there was a significant association between sociodemographic factors, particularly the household income, and the level of attitude towards children and adolescents COVID-19 vaccination. This study revealed that the level of knowledge of parents on COVID19 vaccination for children and adolescents were not satisfactory as almost 30% of the respondents were still categorised as having poor level of knowledge. This called forth the health authorities to spread more information regarding COVID-19 vaccines by promoting its safety and benefits through all media platforms. The results also showed a significant positive correlation between the knowledge level and attitude toward COVID-19 vaccination for children and adolescents so it was believed that enhancement in knowledge level would improve the attitude of parents towards children and adolescents COVID-19 vaccination.